Protein extraction from catfish byproducts and physicochemical properties of the protein isolates. Issue 7 (20th June 2021) - Zhang, Yan; Chang, Sam K. C.
Abstract : Abstract: In order to optimize protein recovery from catfish byproducts by alkaline extraction, the effects of different factors, including particle size, mince‐to‐water ratio, pH, and extraction time were investigated. It was found that a protein recovery of about 30% could be achieved. Increases in pH (pH 10.5, 11, and 11.5) not only improved protein recovery, but also increased protein denaturation evidenced by decreased solubility, decreased α‐helix, increased β‐sheet, and increased random coil. The color and texture of gels made from protein isolate were greatly affected by the pH values used for protein extraction. For the gels made from fillet mince, and protein isolates extracted at pH 10.5, 11, and 11.5, the " L " values were 78.96, 60.38, 57.74, and 54.39, the breaking forces were 205, 492, 585, and 458 g, and deformation values were 10.59, 8.07, 6.73, and 5.04 mm, respectively. Electrophoresis revealed protein degradation during alkali‐aided extraction with MHC, the most predominant band, showing about 50% decrease in comparison with fillet mince. It also demonstrated that gelation not only caused cross‐linking, but also autolysis with 53%, 56%, 59%, and 81% decrease in MHC intensity for fillet mince, protein isolates extracted at pH 10.5, 11, and 11.5, respectively. Fillet mince and protein isolates exhibited different storage modulus patterns during temperature sweep, implying different gelation mechanisms. This study proved the protein extracted from catfish byproducts was potential to be utilized as edible food components especially in gel making. Practical Application: Catfish byproducts, which account for 70% of total weight and 50% of total protein of catfish, are normally used as animal feed, fertilizer, or even waste. This study demonstrated the potential of the utilization of catfish wastes to develop edible food components. This could reduce the total processing waste being discarded into the environment and nutrient loss, therefore increasing profitability of catfish industry.